A Glutathione Activatable Photosensitizer for Combined Photodynamic and Gas Therapy under Red Light Irradiation. Issue 4 (2nd December 2021) - Wang, Ran; Xia, Xiang; Yang, Yanjun; Rong, Xiang; Liu, Ting; Su, Zehou; Zeng, Xiaolong; Du, Jianjun; Fan, Jiangli; Sun, Wen; Peng, Xiaojun
Abstract: Although photodynamic therapy (PDT) is a promising approach for cancer therapy, most existing photosensitizers lack selectivity for tumor cells and the overexpressed glutathione (GSH) in tumor cells reduces the PDT efficiency. Therefore, designing photosensitizers that can be selectively activated within tumor cells and combine PDT with other therapeutic modalities represents a route for precise and efficient anticancer treatment. Herein, an organic activatable photosensitizer, CyI‐DNBS, bearing 2, 4‐dinitrobenzenesulfonate (DNBS) as the cage group is reported. CyI‐DNBS can be uptaken by cancer cells after which the cage group is selectively removed by the intracellular GSH, resulting in the generation of SO2 for gas therapy. The reaction also releases the activated photosensitizer, CyI‐OH, that can produce singlet oxygen ( 1 O2 ) under red light irradiation. Therefore, CyI‐DNBS targets cancer cells for both photodynamic and SO2 gas therapy treatments. The activatable photosensitizer provides a new approach for PDT and SO2 gas synergistic therapy and demonstrates excellent anticancer effect in vivo. Abstract : A photosensitizer CyI‐DNBS is reported which releases SO2 via glutathione activation for gas therapy. Meanwhile, the activated photosensitizer is capable of producing cytotoxic 1 O2 for photodynamic therapy (PDT) under red light irradiation. CyI‐DNBS has demonstrated highly effective therapeutic effects and can significantly inhibit the tumor growth in vivo, providing a new platform for combined PDT and gas therapy.